British Columbia’s Underutilization of Registered Nurse First Assists: A Barrier to Achieving the Quadruple Aim - Bryant, Erin (Operating Room Nurses Association of Canada Journal, 2020)
Registered Nurse First Assists (RNFA) increase surgical efficiency and improve patient care. They have been widely utilized within the United States of America, but utilization in Canada has not been consistent. Currently, Ontario, Quebec, Nova Scotia and select sites in Newfoundland and Labrador have included RNFA as members of their surgical team.1 Through critical analysis, the author discusses how underutilization of this role impacts on healthcare system costs and patient outcomes. Recent surgical strategy policy documents2 have acknowledged the RNFA but full implementation has yet to occur. The aim of the paper is to discuss this role as part of the interdisciplinary team and highlight related policy issues to be addressed prior to increased integration. The author utilizes the Institute for Healthcare Improvement’s “Quadruple Aim”3 as an argument for prioritizing the integration of RNFA and delivering a method of outcome measurement. This discussion provides important rationale for implementing the RNFA role within healthcare facilities and systems to improve health service delivery at all levels. The recommendations present important considerations to improve outcomes at all levels when introducing these roles within individual health authority settings.